Development of Learning Media Based on Geogebra-Assisted Inquiry Learning Models to Improve Students' Mathematical Reasoning Abilities - Silalahi, Joshua Pandapotan; Siagian, Pargaulan; Mukhtar, Mukhtar (Universitas Ma'arif Lampung, 2024)
This research aims to determine the validity, practicality and effectiveness of Geogebra-assisted inquiry learning model-based learning tools developed to improve students' mathematical reasoning. This research is included in development research. This research will be carried out at SMA Negeri 1 Gebang, Jl. Diponogoro, Pekan Gebang, District. Gebang, Kab. Langkat, North Sumatra 20856 for students in class XI Semester I for the 2023/2024 academic year. The research results show that: 1) The tools developed are valid with (a) average validation results for lesson plans of 4.34, teaching materials of 4.23, Student Worksheets of 4.24, mathematical reasoning ability tests of 4.18 . 2) The device developed was categorized as practical with the results of trial I scoring an average of 3.07 (